2019
DOI: 10.1002/lary.27993
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Year Effect of Human Papillomavirus Vaccination on Recurrent Respiratory Papillomatosis

Abstract: Objective To examine whether human papilloma virus (HPV) vaccination in combination with surgical resection could suppress recurrence for an extended period of time in patients with recurrent respiratory papillomatosis (RRP). Methods In a prospective case series, data of patients who received combination therapy comprising surgery and quadrivalent HPV vaccination (Gardasil; Merck & Co., West Point, PA) were collected. Patients were followed up for RRP from March 2012 to July 2018 in an academic tertiary care c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…However, the effectiveness of these adjuvant therapies was not analyzed in this population. Recently, intravenous bevacizumab and HPV vaccination were reported to be clinically effective for the treatment of RRP patients 21,22 . Programmed death‐ligand 1 (PD‐L1) blockade with avelumab demonstrated that its administration was safe and clinically effective in patients with laryngeal RRP but not pulmonary RRP 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of these adjuvant therapies was not analyzed in this population. Recently, intravenous bevacizumab and HPV vaccination were reported to be clinically effective for the treatment of RRP patients 21,22 . Programmed death‐ligand 1 (PD‐L1) blockade with avelumab demonstrated that its administration was safe and clinically effective in patients with laryngeal RRP but not pulmonary RRP 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the model outcomes, vaccinating boys is projected to reduce anal cancer and genital wart incidence in males, and also provide additional protection for females with substantial reductions in the incidence of cervical cancer, precancerous cervical lesions, anal cancer, and genital warts. Although HPV vaccines are not indicated for the prevention of RRP, head and neck cancer, and penile cancer as per label (Gardasil, 2018), there is evidence demonstrating the efficacy of HPV vaccines in reducing persistent HPV infections at these anatomic sites (e.g., persistent external genital infection (Giuliano et al, 2011), persistent oral infection (Herrero et al, 2013;Wilkin et al, 2018), and many countries and international literature considered that HPV vaccines may protect against these diseases, (Takla et al, 2018;Burger et al, 2014;Chesson et al, 2016;Joint committee on Vaccination and Immunization, 2018;Mauz et al, 2018;Boiron et al, 2016;Matsuzaki et al, 2020). Our model suggests GNV with the 9vHPV vaccine is a cost-effective strategy in Flanders (vs. FOV with the 9vHPV vaccine), Wallonia-Brussels (vs. FOV with the 2vHPV vaccine), and the Belgium national catchup program (vs. FOV with the 9vHPV vaccine), with the ICERs being €8,062, €4,179, and €6,127 in the three programs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This biologic understanding of how different arms of the adaptive immune system prevent or control existing infection is in conflict with clinical data suggesting that adjuvant administration of the Gardasil preventative vaccine prevents RRP disease recurrence or significantly lengthens the time between surgeries. Several single cohort, retrospective studies suggest a clinical benefit with increased intersurgery interval after adjuvant Gardasil administration 65,68,69 . Of two multicohort studies that reported intersurgery interval in patients with and without adjuvant Gardasil, one reported clinical benefit and the other did not 70,71 .…”
Section: Immunotherapeutic Strategies For Patients With Rrpmentioning
confidence: 99%